DykeSpeak : lesbian news & views from San Francisco to New York City. (San Francisco : DykeSpeak.)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 4104 24th Street, San Francisco, CA94114
Engels
Periodiek